2017
DOI: 10.21273/hortsci11903-17
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Rate of Organic Fertilizer during the Vegetative-stage for Cannabis Grown in Two Coir-based Substrates

Abstract: Cannabis producers, especially those with organic operations, lack reliable information on the fertilization requirements for their crops. To determine the optimal organic fertilizer rate for vegetative-stage cannabis (Cannabis sativa L.), five rates that supplied 117, 234, 351, 468, and 585 mg N/L of a liquid organic fertilizer (4.0N–1.3P–1.7K) were applied to container-grown plants with one of two coir-based organic substrates. The trial was conducted in a walk-in growth ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 30 publications
3
79
0
Order By: Relevance
“…Increased interest in CBD has led to increased cultivation of hemp, but because hemp has been selected for fiber and seed production, it is generally low in CBD content (2% to 4%) (Mead, 2017). Therefore, the development of hemp cultivars with increased CBD content is a current breeding objective (Caplan et al, 2017;Soler et al, 2017).…”
mentioning
confidence: 99%
“…Increased interest in CBD has led to increased cultivation of hemp, but because hemp has been selected for fiber and seed production, it is generally low in CBD content (2% to 4%) (Mead, 2017). Therefore, the development of hemp cultivars with increased CBD content is a current breeding objective (Caplan et al, 2017;Soler et al, 2017).…”
mentioning
confidence: 99%
“…However, the lower capacity (U2-HP) growing medium produced 11% higher floral dry weight, 13% higher growth index, 20% higher THC yield, and 20% higher CBGA yield than the one with higher capacity (U2) [49]. The increases may be attributed to the higher irrigation frequency (17 times in U2-HP and 13 times in U2), which was necessary for maintaining moisture (30%), and/or high root zone oxygen, which positively affects plant health, nutrient uptake, root growth, and root-bone disease prevention [49]. Hydroponic systems have greater control over the growing environment by delivering a full range of nutrients to the roots.…”
Section: Growing Conditionsmentioning
confidence: 93%
“…Extractable soil P was negatively correlated with CBD concentrations in leaf tissue [48]. Another study showed that there was no difference in floral material yield between two organic coir-based growing media, which had distinct water-holding capacities [49]. However, the lower capacity (U2-HP) growing medium produced 11% higher floral dry weight, 13% higher growth index, 20% higher THC yield, and 20% higher CBGA yield than the one with higher capacity (U2) [49].…”
Section: Growing Conditionsmentioning
confidence: 99%
See 2 more Smart Citations